Towards Inclusive Tourism Governance: Social Inequality and Community Representation in Soppeng Tourism Villages - Irwan; Djohar; Badrus Zaman, Akhmad Roja (CV. Literasi Indonesia, 2025)
This article analyzes social inequality and community representation in the governance of tourism villages in Soppeng Regency, South Sulawesi. The research used a qualitative approach with an exploratory case study design in three tourist villages: Lompulle, Bulue, and Mattabulu. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using reflexive thematic analysis techniques. The results showed that local social structures play a central role in determining policy direction, benefit distribution, and tourism decision-making. Community participation is collective yet hierarchically structured, while informal mechanisms such as customary deliberations serve as a means of conflict resolution. The involvement of women and youth tends to be limited to operational functions, not at the strategic level. These findings show that the seemingly participatory governance of tourism villages is actually still trapped in patronistic logic and structural exclusion. Therefore, this study recommends the importance of policy interventions that strengthen inclusive representation and equitable distribution of power to support sustainable tourism development based on social justice.